(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
This study aims to explore Politics of Digitalization in the Management of Educational System in Nigeria. Considering the politics surrounding the digitalization of education in Nigeria which is complex and multifaceted, this study observed the influence of Nigeria politics on Educational digitalization, the role of public – private partnership in the digitalization of Education in Nigeria and challenges in digitalizing Nigerian. Education, Conclusion and recommendations were also made.